Golpe versus impeachment: uma análise crítica das construções discursivas polarizadas em torno da destituição da presidenta Dilma Rousseff. - Rocha, Daniel França da (2021)
This research proposes a scientific investigation about the polarized discursive constructions around the dismissal of Dilma Rousseff from the Presidency of the Republic of Brazil, in 2016, marked by the terms Coup and Impeachment. Critical Discourse Analysis through Norman Fairclough's Three-Dimensional Model was used as theoretical and methodological framework. From the question of how these conflicting discursive constructions interfered in the modus operandi of Brazilian democracy, the objective was to analyze these discursive constructions in and by the media, characterizing them as social and discursive practices. This analysis sought to identify, through the concepts of Hegemony and Ideology, the intentionalities of the social actors that produce these discourses. The study also seeks to relate aspects of Dilma's dismissal with the institutional crisis of the Brazilian state. The research has as corpus a qualitative sample of 14 texts published by magazines, newspapers, portals and blogs over the years 2015 and 2016, a time interval in which the discursive dispute over the meaning of the dismissal process took place. Categories of said Three-Dimensional Model are applied. The conclusion points to such a social-discursive practice as a maneuver to reestablish known power relations by making dominant social groups effective as leaders.